Effects of Attention-Boosting Exercises on the Academic Performance of Grade Two Pupils - Relente, Ginia (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the effects of attention-boosting exercises on the academic performance of Grade Two pupils in selected public elementary schools in the District of Binangonan during the School Year 2025–2026. The participating schools included Bilibiran, Binangonan, Calumpang, Casimiro A. Ynares Sr., Darangan, Doña Susana Madrigal, Libis, Libid, Lunsad, Mabuhay Homes 2000, Macamot, Mahabang Parang, Pilapila, and Tatala Elementary Schools.The respondents were the total population of 100 Grade Two teachers, described by age, sex, civil status, educational attainment, position, length of service, and in-service trainings attended. Using a researcher-made questionnaire-checklist and documentary analysis of pupils’ First Quarter grades (School Form 9), the study examined the perceived impact of attention-boosting exercises on cognitive improvement, knowledge competency, skills competency, and transfer of learning. A descriptive research design was applied.Results showed that teachers perceived attention-boosting exercises to significantly enhance pupils’ cognitive, knowledge, and skills competencies. Most respondents were female, aged 41–50 years, married, Teacher I holders, with a Bachelor’s degree and 10–14 years of experience, having attended national-level trainings. Perceptions did not significantly differ by age, sex, educational attainment, position, or length of service, but civil status and in-service trainings influenced certain aspects. Pupils’ academic performance was very satisfactory (mean = 87.66), with no significant relationship between teachers’ perceptions and actual performance.The study recommends conducting targeted in-service trainings, incorporating attention-boosting exercises into lesson plans, applying short engaging activities to sustain focus, and exploring related variables in future studies.
Keywords: attention-boosting exercises, academic performance, Grade Two pupils, cognitive improvement, knowledge competency, skills competency, transfer of learning